Sosialisasi dan Edukasi Produk Keuangan Syariah Bagi Penguatan UMKM di Cinere Depok - Faisal Marzuki; Faizi Faizi; Ayunita Ajengtiyas Saputri Mashuri (Gapenas Publisher, 2022)
MSME players in Indonesia must be literate in information on Islamic financial products, the number of which is very varied and complex. For example, the financing of Mudharabah, Musyarakah, Istisna', Salam, Ijarah, Qard, Rahn, and so on (Zaini et al., 2019). The complexity of this sharia contract must be massively and systematically socialized to our MSME actors, which are very large in number. The goal is not only to improve the quality of Islamic financial literacy, but also as a means of obtaining convenience in obtaining complete and useful information about the availability of Sharia financing products and the application mechanism in obtaining this service so that the needs of capital fulfillment, business development for MSMEs or other consumptive needs can be met with sharia schemes in accordance with Islamic principles (Faizi & Shuib, 2021). Information like this has not been obtained by the public, especially MSME actors